Fundamentals of Entrepreneurship ENT 300 : Mayesa Ladies Salon / Farah Inesa Noor Iskandar...[et al.] - Noor Iskandar, Farah Inesa; Brahim, Mohd Aqmal Ashyraf; Ramlee, Siti Nasyuha; Tony, Stephenie (2013)
Inspired by the increasing desires of modern female being to look for a secure hair salon, Mayesa Ladies Salon has been created to offer hair and also hijab service. We seek to fulfil the fardhu-kifayah obligatory by giving our (Muslimah) clienteles the opportunity to enjoy every second at our salon with a piece of mind, ensuring their aurat is unexposed to those non-rightful ones (including the non-Muslim female hair stylist). Mayesa is a hair salon located in Lot 6290, Block 26, Muara Tuang Land District, Jalan Datuk Mohd Musa, 94300, Kota Samarahan Kuching, Sarawak. Mayesa serves only women and accepts appointments as well as walk-ins.